The PECC Framework: Promoting Gender Sensitivity and Gender Equality in Computer Science Education - Bernadette Spieler; Carina Girvan (Computers, 2025)
There are increasing expectations that we should live in a digitally and computationally literate society. For many young people, particularly girls, school is the one place that provides an opportunity to develop the necessary knowledge and skills. This environment can either perpetuate and reinforce or eliminate existing gender inequalities. In this article, we present the “PLAYING, ENGAGEMENT, CREATVITIY, CREATING” (PECC) Framework, a practical guide to supporting teachers in the design of gender-sensitive learning activities, bringing students’ own interests to the fore. Through a six-year, mixed-methods, design-based research approach, PECC—along with supporting resources and digital tools—was developed through iterative cycles of theoretical analysis, empirical data (both qualitative and quantitative), critical reflection, and case study research. Exploratory and instrumental case studies investigated the promise and limitations of the emerging framework, involving 43 teachers and 1453 students in secondary-school classrooms (including online during COVID-19) in Austria, Germany, and Switzerland. Quantitative data (e.g., surveys, usage metrics) and qualitative findings (e.g., interviews, observations, classroom artefacts) were analyzed across the case studies to inform successive refinements of the framework. The case study results are presented alongside the theoretically informed discussions and practical considerations that informed each stage of PECC. PECC has had a real-world, tangible impact at a national level. It provides an essential link between research and practice, offering a theoretically informed and empirically evidenced framework for teachers and policy makers.